DC unmade: failure, fandom and the Justice League films that could have been - Greene, Ryan, author; Diffrient, David Scott, advisor; Martey, Rosa, committee member; Burgchardt, Carl, committee member; Elkins, Evan, committee member (Colorado State University. Libraries, 2024)
Unmade films have received little attention as a general category, and this is doubly so for unmade superhero genre projects. The fact that these unfilms are failures in otherwise vibrant action franchises has typically led to their elision from canonical narratives. In studying two of the many defunct superhero films in Warner Brothers's DC catalog, it is possible to compare the failures of each in order to discern the industrial and narrative practices that contributed to their collapse. I apply scholarship on failure and comic book film adaptation to the case of George Miller's Justice League: Mortal. I trace the director's grand vision of a franchise juggernaut that was ultimately cancelled due to a confluence of bureaucratic interference and backlash against the promise of unlimited, speculative success. I then turn attention toward WB's second attempt to create a superhero ensemble film, Zack Snyder and Joss Whedon's Justice League (2017). From the ashes of the film's financial under-performance and critical failure rose a dogged fan movement to release an unknown and totally different director's cut. To understand this fan community and its impact on unproduction, I evaluate the Snyder Cut movement's defense of Zack Snyder's unmade DC Extended Universe, their battle against Warner Brothers and their refusal to accept failure. Taken together, these two unproductions demonstrate two divergent visions of failure. One lacked fan backing and so rests inert, its pieces scattered across the internet. The other rose from the unfinished realm of shadow cinema, lifted up by fans who vilified its producer while demanding that executives pay for its release.
Keywords: comic book movies; fandom; unproduction; failure; adaptation; superheroes